Intermediate model based efficient and integrated multidisciplinary simulation data visualization for simulation information reuse. (December 2015) - Shao, Yanli; Liu, Yusheng; Li, Chunguang
Highlights: An intermediate model is designed for multidisciplinary simulation data integration. The hybrid mesh size field controls the generation of intermediate mesh model. Several strategies are proposed to improve the data transmission efficiency. A content-based retrieval method is developed to find simulation models rapidly. Abstract: The efficient and integrated visualization and reuse of multidisciplinary simulation data are imperative for the development of complex products. However, it is not a trivial task for designers to efficiently acquire, view and then reuse simulation data to improve the product design process. The challenge is that simulation data are always too huge to be transferred and retrieved quickly and they tend to be heterogeneous and tool-specific due to the lack of a uniform representation. In this study, an approach of intermediate model based efficient and integrated visualization of multidisciplinary simulation data for simulation information reuse is proposed to address the above issues. Firstly, the intermediate model based integrated model framework is designed to support the uniform modeling and integrated visualization of multidisciplinary simulation data. Then, the intermediate mesh model is constructed based on the hybrid mesh size (HMS) field to achieve the uniform representation of multidisciplinary simulation data with high-fidelity. Thirdly, a series of strategies such as coarse filtering, fine filtering for incremental transmission and data compression are proposed to improve data transmission efficiency. Moreover, a simulation model descriptor (SMD) based similarity assessment method is developed to support the efficient retrieval of simulation models for reuse. Finally, several experiments are conducted to demonstrate the feasibility and effectiveness of the proposed model and methods.